👤

aduceti la o forma mai simpla b)(x+y)(x-y)-(x la 3 +yla 2)=
c) 2a (a+1)-(a-2)(a+4)=
d) (y+2) la 2 - 2y(y+2)=


Răspuns :

b)(x+y)(x-y) -(x la 3+y la 2)
=x la 2-y la 2 - x(x la+2+y la
2
=x la 2-y la 2 - x la +y la 2
=0(simplifici x la cu -x la 2 si -y la 2 cu y la 2)
c)2a(a+1)-(a-2)(a+4)
=2a la 2 + 2a - a la2+4a-2a +6
=a la 2+2a +6
d)(y+2) la 2 -2y(y+2)
=y la 2 + 4y +4 -2y la 2 + 4y
= -y la 2+8y +4 =(-y-2) la 2
[tex]b)(x+y)(x-y) -( x^{3} + y^{2} )=\ \textgreater \ x^{2} - y^{2} -x( x^{2} - y^{2} )=\ \textgreater \ x^{2} - y^{2} [/tex][tex]- x^{2} + y^{2} =\ \textgreater \ 0[/tex]
[tex]c)2a(a+1)-(a-2)(a+4)=\ \textgreater \ 2a^{2} +2a- a^{2} +4a-2a+6=\ \textgreater \ a^{2} +2[/tex][tex]a+6[/tex]
[tex]d)(y+2) ^{2} -2y(y+2)=\ \textgreater \ y^{2} +2*y*2+ 2^{2} -2y^{2} +4y=\ \textgreater \ -y^{2} +8y+[/tex][tex]4=\ \textgreater \ (-y-2) ^{2} [/tex]